G6PC2 confers protection against hypoglycemia upon ketogenic diet feeding and prolonged fasting - Karin J. Bosma; Mohsin Rahim; James K. Oeser; Owen P. McGuinness; Jamey D. Young; Richard M. O'Brien (Elsevier, 2020)
Objective: G6PC2 is predominantly expressed in pancreatic islet beta cells. G6PC2 hydrolyzes glucose-6-phosphate to glucose and inorganic phosphate, thereby creating a futile substrate cycle that opposes the action of glucokinase. This substrate cycle determines the sensitivity of glucose-stimulated insulin secretion to glucose and hence regulates fasting blood glucose (FBG) but not fasting plasma insulin (FPI) levels. Our objective was to explore the physiological benefit this cycle confers. Methods: We investigated the response of wild type (WT) and G6pc2 knockout (KO) mice to changes in nutrition. Results: Pancreatic G6pc2 expression was little changed by ketogenic diet feeding but was inhibited by 24 hr fasting and strongly induced by high fat feeding. When challenged with either a ketogenic diet or 24 hr fasting, blood glucose fell to 70 mg/dl or less in G6pc2 KO but not WT mice, suggesting that G6PC2 may have evolved, in part, to prevent hypoglycemia. Prolonged ketogenic diet feeding reduced the effect of G6pc2 deletion on FBG. The hyperglycemia associated with high fat feeding was partially blunted in G6pc2 KO mice, suggesting that under these conditions the presence of G6PC2 is detrimental. As expected, FPI changed but did not differ between WT and KO mice in response to fasting, ketogenic and high fat feeding. Conclusions: Since elevated FBG levels are associated with increased risk for cardiovascular-associated mortality (CAM), these studies suggest that, while G6PC2 inhibitors would be useful for lowering FBG and the risk of CAM, partial inhibition will be important to avoid the risk of hypoglycemia.